현장중심의 효율적 재난통신체계 수립 방안 연구 - Kim, Yongsoo; Kim, Dongyeon (한국재난정보학회 논문집, 10(4), 2014)
Our society is changed and diversified rapidly and such tendency is accelerated day after day and has made a lot of problems in the many fields. The important thing we have to recognize is such tendency has a bad effect recently on the safety system in Korea. So it is time to enhance the national safety system and moreover recently Sewol-ho(passenger ship) went down in the sea, it made people remind the importance of national safety system. With this incident, Korean government decided to establish the national safety communication network against the disaster. At this time, I will propose several ideas about the national safety communication network. 1. It must to be established an unified network to contact people who is on a disaster site anytime and anywhere. This is most important element on all disaster sites. 2. PS-LTE technology must to be adopted to the network because it has many advantages including various multimedia services compared to the TETRA in the past. 3. 700MHz is the most efficient band for the network because it has wide cell sites coverage compared to 1.8GHz. 4. Satellite communication system is needed to the network for back-up. 5. It will be effective to adopt Social Media to the communication network system like a Twitter or Facebook for sharing many kinds of information and notifying people of warning message. 6. It can make the network more useful to introduce the latest technology like a sensor network. And Korean government has to improve the system related to the disaster including law and operating organization. 우리나라는 고속의 경제성장을 이룩해 오면서 경제적, 사회적으로 성장이란 관점에 초점을 맞추어 왔고 그 결과 세계 선진국 대열에 근접하였다. 그러나 지금 우리는 국가 전체적으로 재난과 안전이란 문제에 직면에 있다. 국가재난관리체계와 그에 대한 시스템, 국민의 안전의식은 여전히 후진국 수준에 머물러 있었음이 드러났고 이것은 최근 세월호 사건으로 극명하게 표출되면서 정부와 국민 모두에게 큰 자각심을 불러 일으켰다. 또한 이전과 달리 재난은 환경적, 사회적 등의 변화로 더욱 대형화, 복잡화, 다변화됨과 동시에 예측이 불가능한 형태로 바뀌어 가고 있다. 이와 같은 변화에서 재난현장을 중심으로 한 신속하고 효율적인 대응의 중요성이 그 어느 때보다 절실하게 요구되고 있다. 이러한 시대적 요구를 실현하기 위해서는 국가적 차원에서의 재난현장 중심의 일원화된 재난통신망 구축과 재난대응관리에 대한 법, 제도, 조직 개선 및 고도화된 재난대응표준절차 수립이 필요하다. 재난현장 중심의 효율성을 확보한 일원화된 재난통신망을 구축하기 위해서는 현장에 투입된 유관기관 담당자들 간의 원활한 통신확보, 다양한 현장 정보입수, 정보공유, 통신 불감지역 최소화, 정확한 현장 대응을 위한 신속한 의사결정, 통신두절 대비 백업망 구축 등이 필수적인 요소이다. 이를 위해 음성통신 외에 영상을 포함한 다양한 멀티미디어 통신과 위치정보 파악이 가능하고 우리나라가 약 70% 원천 기술을 보유한 PS-LTE 방식을 이용한 통신망 구축이 최적으로 판단된다. 또한 주파수 특성상 통신 불감지역이 최소인 700MHz 대역을 이용하고 예측할 수 없는 통신두절에 대비한 위성통신백업망과 재난현장의 많은 정보 입수를 위해 센서 네트워크 기술, 소셜미디어 활용 등을 통하여 신속하고 정확한 의사결정과 현장대응 및 일사분란한 지휘통신체계로 피해를 최소화 할 수 있다. 이와 동시에 재난대응 관리 측면에서는 첫째로 재난관리 표준운영절차를 선진화, 고도화하여 재난발생시 f즉각적인 행동절차에 돌입하게 하며 둘째로 개방형 플랫폼 형태의 재난통합대응체계를 구성하여 민관이 공동으로 재난대응에 참여할 수 있도록 한다. 셋째로 법, 제도, 업무분산에 의한 총괄조정기능을 강화하여 적극적인 재난안전관리를 도모한다. 넷째로 국무총리 산하에 별도의 재난대응 전담조직이 필요한데 해당업무의 특성이나 규모를 고려하여 소방이 적합한 조직으로 사료된다. 다섯째로 인명 구조를 위한 특수구조단체 설립이 필요하고 여기에는 현재 중앙 119구조대를 확대, 개편하는 것이 바람직하다. 마지막으로는 현재의 복잡한 긴급구조통신번호를 119로 통합하고 이에 대한 통합센터 신설과 전문인력 양성에도 많은 정부의 노력이 필요할 것으로 사료된다.